2020
DOI: 10.1080/15538362.2020.1772178
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Genetic Diversity in Some Non-commercial Cultivars of Musa L. from Assam, India, Using Morphometric and ISSR Markers

Abstract: Northeast India is known for its diverse nature of soil, climate, and topography that supports rich banana diversity. Banana (Musa sp.) is the second most important fruit crop in India due to its availability throughout the year, taste along with the nutritive and medicinal value. Thus, the genetic diversity of banana resources is essential for present and future food. This study aimed to determine the comparative genetic variation among 14 non-commercial edible banana cultivars of Assam, India, by using 50 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The genetic diversity of bananas has been carried out using different molecular markers, and significant success has been made for analyzing commercial cultivars and some wild germplasm 34 , 35 . However, not much is known about the local germplasm, which harbors important traits for adaptation to local climatic conditions and small-holdings.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic diversity of bananas has been carried out using different molecular markers, and significant success has been made for analyzing commercial cultivars and some wild germplasm 34 , 35 . However, not much is known about the local germplasm, which harbors important traits for adaptation to local climatic conditions and small-holdings.…”
Section: Resultsmentioning
confidence: 99%
“…The only study that showed within-group variation in the AAA Cavendish bananas was reported by Ermini et al (2018) [34]. On the contrary, as expected, greater genetic diversity has been described for studies that used a mixed group of species or subgroups of bananas [6,10,29,[35][36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 88%
“…The exploitation of genetic diversity plays a pivotal role in determining the success of breeding program (Borborah et al, 2020). Populations that actively display signi cant levels of genetic variation are particularly valuable, as they can expand the genetic diversity in any breeding program (Nachimuthu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%